2016
DOI: 10.1007/s11682-016-9562-1
|View full text |Cite
|
Sign up to set email alerts
|

Gray matter volume and dual-task gait performance in mild cognitive impairment

Abstract: Dual-task gait performance is impaired in older adults with mild cognitive impairment, but the brain substrates associated with dual-task gait performance are not well-established. The relationship between gray matter and gait speed under single-task and dual-task conditions (walking while counting backward) was examined in 560 seniors with mild cognitive impairment (non-amnestic mild cognitive impairment: n = 270; mean age = 72.4 yrs., 63.6 % women; amnestic mild cognitive impairment: n = 290; mean age = 73.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
34
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 73 publications
6
34
1
Order By: Relevance
“…Structures comprising the GM networks associated with NPW speed in older adults without dementia reported in this study are consistent with aspects of existing literature (Allali et al, ; Callisaya et al, ; Doi et al, ; Ezzati, Katz, Lipton, Lipton, & Verghese, ; Nadkarni et al, ; Rosano et al, ). Broadly, these similarities indicate that single‐task gait speed is associated with GM networks composed of structures in both the motor and the control pathways of locomotion (Leisman, Moustafa, & Shafir, ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Structures comprising the GM networks associated with NPW speed in older adults without dementia reported in this study are consistent with aspects of existing literature (Allali et al, ; Callisaya et al, ; Doi et al, ; Ezzati, Katz, Lipton, Lipton, & Verghese, ; Nadkarni et al, ; Rosano et al, ). Broadly, these similarities indicate that single‐task gait speed is associated with GM networks composed of structures in both the motor and the control pathways of locomotion (Leisman, Moustafa, & Shafir, ).…”
Section: Discussionsupporting
confidence: 92%
“…One reason for increasing DTC with aging is age‐related atrophy in the brain, which follows a variable course. In addition to interindividual variability in the overall patterns of GMV atrophy, population‐wide studies have shown that some areas, such as the PFC, atrophy more than others (Doi et al, ; Dumurgier et al, ; Storsve et al, ). One other study (Allali et al, ) has looked at the GMV networks associated with walking speed during dual‐task performance.…”
Section: Discussionmentioning
confidence: 99%
“…Further functional imaging studies are warranted to investigate the specific roles of these regions in dual task performance and automaticity. In general, our findings on cognitive-relevant brain volumes are consistent with other research showing that decreased volume is associated with a worse performance during DT in those with cognitive impairment (Doi et al 2017). They also highlight the utility of DT performance metrics beyond mDTE as has been suggested in other populations (Longhurst and Landers 2019;Plummer and Eskes 2015;Plummer et al 2013;Yang et al 2017).…”
Section: Discussionsupporting
confidence: 91%
“…Likewise, there is little known about the relationship between DT function and cognitive relevant brain areas. Previous studies have identified brain areas uniquely correlated with DT performance, including frontal, temporal, and cingulate regions (Doi et al 2017;Tripathi et al 2019). While not the hallmark of cognitive disorders, there is evidence of decreased volume, decrease neuronal integrity, and lower cerebral blood flow in motor-related brain areas such as the basal ganglia and primary motor cortex in those with MCI and dementia, and these findings have been shown to be associated with both single and dual task gait variability (Annweiler et al 2013;Jiji et al 2013;Nakamura et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these functional compensation mechanisms might be linked to the natural occurrence of brain atrophy during lifetime. Previous studies showed that PFC atrophies more than other regions ( Dumurgier et al, 2012 ; Storsve et al, 2014 ; Doi et al, 2017 ) and is also often functionally underutilized with age ( Holtzer et al, 2011 ). Several studies showed an association of DT performance (i.e., processing speed and executive function) and the gray matter volume of various areas of motor control including PFC ( Allali et al, 2019 ; Blumen et al, 2019 ; Tripathi et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%